Collecting with “botanical friends”: Four Women in Colonial Quebec and Newfoundland - Shteir, Ann; Cayouette, Jacques (Scientia Canadensis, 2019)
Four women from the British colonial elite in Quebec and Newfoundland were among the more than 120 contributors to William Jackson Hooker’s Flora Boreali-Americana (1829-40), an imperial project to assemble information about plants from across British North America. Letters that Christian Ramsay (Lady Dalhousie), Anne Mary Perceval, Harriet Sheppard, and Mary Brenton wrote to Hooker during the 1820s and 1830s show their interest in collecting Canadian plants — native orchids, ferns, weeds, bog plants — as well as their zeal for sharing knowledge and communicating their findings among friends and across borders. Along with other archival materials now available, the letters are a record of work by women in botanical discovery. By making visible the friendships, networks, and social and cultural practices that brought the women into Hooker’s project, the letters enlarge and enrich the history of science in Canada.